Plastics engineered product design - Rosato, Dominick V. (Elsevier Advanced Technology, 2003)
& bull; A comprehensive book which collates the experience of two well-known US plastic engineers. & bull; Enables engineers to make informed decisions. & bull; Includes a unique chronology of the world of plastics. The use of plastics is increasing year on year, and new uses are being found for plastics in many industries. Designers using plastics need to understand the nature and properties of the materials which they are using so that the products perform to set standards. This book, written by two very experienced plastics engineers, provides copious information on the materials, fabrication processes, design considerations and plastics performance, thus allowing informed decisions to be made by engineers. It also includes a useful chronology of the world of plastics, a resource not found elsewhere.